Banding for access related ischaemia: Our experience in Kuantan, Malaysia - Abdul Rahman, Mohd Norhisham Azmi; Othman, Ahmad Faidzal (The Editorial Committee of Annals of Vascular Diseases, 2014)
We reviewed our result of banding procedures for steal syndrome identied from theatre lists and cross referenced with the theatre log book. We performed 8 banding procedures in 8 patients, between June 2012 and April 2014. All presented with grade II–III steal syndrome. Complete symptoms resolution and salvage access occurred in all cases except in 1 patient. We concluded, employing banding as a flow limiting procedure has been a success in dealing with access related ischaemia.